Volatile chemical composition of Colombian Plectranthus amboinicus (Lour.) Spreng essential oil and its biocidal action against Tribolium castaneum (Herbst) - Jaramillo-Colorado, Beatriz Eugenia; Vega-Díaz, Rafael; Pino-Benítez, Cruz Nayibe (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2022)
Plectranthus amboinicus (Lour.) Spreng is an herbaceous and aromatic plant that belongs to the Lamiaceae family. In this research work, the repellent and insecticidal activity of the essential oil (EO) of P. amboinicus from the Condoto township in the department of Choco (Colombia) against the flour weevil Tribolium castaneum (Herbst) was studied. EO was isolated by the hydrodistillation technique. The identification of the volatile metabolites of P. amboinicus EO was done through gas chromatography coupled to mass spectrometry (GC / MS). The contact method was used for the bioassay of the essential oil’s repellent and fumigant activities. In the Plectranthus amboinicus EO, fifteen compounds were found. The major compound was carvacrol (75.9%) followed by α-bergamotene, p-cymene, α-humulene, 4-terpineol, caryophyllene oxide, β-guaiene, 1-octen-3-ol, α-muurolene, caryophyllene, 3-hexen-2-ol, γ-terpinene, isothymol, 2-carene and β-bisabolene, respectively. The highest repellent activity obtained was 83.33 and 9.67% at a concentration of 0,1% with exposure times of 2 and 4 hours, respectively. The fumigant activity was 100% at a concentration of EO 250 μL L-1. The results indicated that the natural compounds tested may be useful alternatives to control T. castaneum infestation.